CHLOROPHYLL-A SPREAD ANALYSIS USING MERIS AND AQUA MODIS SATTELLITE IMAGERY (Case Study: Coastal Waters of Banyuwangi) - Taufik, Muhammad; Wiliyanto, Nico (Departemen Teknik Geomatika ITS, 2016)
Indonesian is the archipelago country, 2/3 of the total area of Indonesia is the ocean. Oceans become a source of life for Indonesia people, including in the region of Banyuwangi. The potential of marine products in Banyuwangi regency not only fish, but also there are squid, crab, shellfish and others. Existence of fish can not be separated from the marine ecosystem, especially the food producers who are in the sea, the chlorophyll-a in phytoplankton. Information used to obtain the distribution of chlorophyll-a concentration value can be obtained from the data processing Aqua MODIS and Envisat Meris satellite imagery; which is reinforced by in situ data in the form of sea water sampling tested in the laboratory. Image processing using algorithms ATBD-19 for the Aqua MODIS imagery and algorithms Case-2 Water Processor (C2WP) for Envisat MERIS imagery. From this research, obtained a map of the distribution of chlorophyll-a concentrations in coastal waters of Banyuwangi generated from satellite image processing and analysis of several in situ data, based on the parameters of chlorophyll-a concentration. These results can be concluded that Aqua MODIS has a strong enough correlation to data in situ, with a correlation coefficient of r2 amount 0.5495. While the correlation between data in situ with Envisat MERIS imagery is quite weak with r2value amount 0.3782.